Dampak Lalu Lintas Akibat Aktivitas Best Western Coco Hotel Terhadap Kinerja Ruas Jalan Basuki Rahmat Palu - Pratama, Aditya Bayu; Tahir, Anas; Mashuri, Mashuri (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2015)
Palu, the capital city of Central Sulawesi province is experiencing economic progress. Progress is shown by the supporting facilities such as one of the biggest hotel in Palu that is Best Western Coco Hotel at Basuki Rahmat Street.The existence of this hotel will increase human activities towards the hotel by using a vehicle, so that could increase the amount of vehicles in this area. The total additional volume of these vehicles can cause additional traffic load in Basuki Rahmat Street and influence its performance. This study was aims to determine the performance of Basuki Rahmat road on the existing condition and in the future without and with activity affected the hotel. The analysis conducted by using the method of Indonesian Highway Capacity Manual, 1997. In this research a survey of traffic volume, side barrier and the vehicle travel time were conducted. The survey was conducted on Thursday, September 4th 2014. Base on the result of analysis on theÂ  performance of Basuki Rahmat Street, without development for existing condition the value was obtained as DS = 0,30 andÂ  DS on 2014 condition = 0,47 by level of services (LOS) C. While the conditions of the development of the area obtained value of DS=0.31, DS condition 2014 = 0,48 by level of services (LOS) = C. The handling of road start from additional of median on the road section will continue to maintain the performance of roads in a state with a level of service B, by degree of Saturation in each direction in 2024 is 0.44 and 0.41.